The impact of improvement of water supply and sanitation facilities on diarrhea and intestinal parasites: a Brazilian experience with children in two low-income urban communities O impacto das medidas de melhoria do abastecimento de água e esgoto sobre a diarréia e parasitose intestinal: experiência brasileira com crianças de comunidades de baixa renda - Rainer Gross; Bernd Schell; Maria Carmen Bisi Molina; Maria Antonia Cuelho Leão; Ulrike Strack (Universidade de São Paulo, 1989)
During the second half of 1986 the impact of the improvement of water supply and excreta disposal facilities on diarrheal diseases and intestinal parasitosis was studied in 254 children up to six years of age from two favelas (shanty towns) of Belo Horizonte, Brazil. The estimated incidence of diarrhea was 6.2 episodes/child year and the estimated period prevalence reached 31.0 episode days/ child/ year. The point prevalence of parasitosis was 70.7% (Ascaris lumbricoides: 55.4%, Trichuris trichiura: 19.6%, Giardia lamblia: 17.9%). The estimated prevalence of diarrhea decreased with improvement of water supply and sanitation facilities to 45% and 44% respectively, but no statistically significant impact was observed in the case of parasitosis. School education and weaning practice were found to be other important determinants of diarrhea. Em 1986 pesquisou-se, junto a 254 crianças de até 6 anos de idade, residentes em duas favelas de Belo Horizonte (Brasil), o impacto das medidas de melhoramento do abastecimento de água e esgoto na incidência de diarréia e parasitose intestinal. Até então, a incidência de diarréia era estimada em 6,2 casos por criança e ano, com uma duração predominante de 31,0 dias por caso/criança/ano. A taxa de difusão de parasitose alcançava 70,7% (Ascaris lumbricoides: 55,4%, Trichuris trichiura: 19,6%; Giardia lamblia: 17,9%). Após os melhoramentos no abastecimento de água e esgoto, a incidência de diarréia caiu para 45% e 44%, respectivamente. Quanto à parasitose, entretanto, não se constatou nenhum impacto estatisticamente significante. Também verificou-se que o grau de educação escolar e práticas de desmame são determinantes de grande importância na incidência de diarréia.